2021
DOI: 10.1021/acsapm.1c00121
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl chloride)-Based Anion-Exchange Membrane with High-Antifouling Potential for Electrodialysis Application

Abstract: The development of facile approaches to fabricate cost-effective anion-exchange membranes (AEMs) with desirable antifouling potential can promote wider AEM-based applications. In this work, we report an easy method for the preparation of AEMs using cost-effective poly(vinyl chloride) (PVC) via immersing the PVC films in triethylenetetramine (TETA) solution under mild conditions. The as-prepared AEMs with low surface area resistance in a range of 1.33−5.94 Ω•cm 2 have the crosslinking structure, possessing good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…In addition, Freger et al 16 also found that grafting poly(ethylene glycol) on the surface of polyimide membranes improved the hydrophobicity of the polyimide membrane surface and the antifouling performance was also greatly improved. Liu et al 17 enhanced the antifouling performance of the cross-linking membranebased poly(vinyl chloride) (PVC) by avoiding π−π interactions between pollutants and the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Freger et al 16 also found that grafting poly(ethylene glycol) on the surface of polyimide membranes improved the hydrophobicity of the polyimide membrane surface and the antifouling performance was also greatly improved. Liu et al 17 enhanced the antifouling performance of the cross-linking membranebased poly(vinyl chloride) (PVC) by avoiding π−π interactions between pollutants and the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The smooth morphology (dark hydrophilic region) observed for the PVC membrane was cross-linked with triethylenetetramine (TETA), followed by quaternization with an 8 h process in 0.1 M NaCl. 129 In contrast, the dark hydrophilic region was not observed clearly for the 14 h process due to ion suppression.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 98%
“…However, combining copolymers via this method is expensive due to the extensive use of chemicals, the reaction under low temperatures (−15 to 0 °C), and the timeconsuming and multistep procedures. The one-step, low-cost process of aliphatic polymer PVC-based AEMs (e.g., PVC45) was recently developed by Liu et al 129 PVC was dissolved in DMAc at 60 °C with stirring. Aerward, the dissolved solution was cast onto the glass and directed at 60 °C overnight to prepare the membrane.…”
Section: Hydrocarbon-based Aemsmentioning
confidence: 99%
See 2 more Smart Citations